Th1-biased immunomodulation and therapeutic potential of Artemisia annua in murine visceral leishmaniasis. - Mohammad Islamuddin; Garima Chouhan; Abdullah Farooque; Bilikere S Dwarakanath; Dinkar Sahal; Farhat Afrin (Public Library of Science (PLoS), 2015)
BACKGROUND:In the absence of vaccines and limitations of currently available chemotherapy, development of safe and efficacious drugs is urgently needed for visceral leishmaniasis (VL) that is fatal, if left untreated. Earlier we reported in vitro apoptotic antileishmanial activity of n-hexane fractions of Artemisia annua leaves (AAL) and seeds (AAS) against Leishmania donovani. In the present study, we investigated the immunostimulatory and therapeutic efficacy of AAL and AAS. METHODOLOGY/PRINCIPAL FINDINGS:Ten-weeks post infection, BALB/c mice were orally administered AAL and AAS for ten consecutive days. Significant reduction in hepatic (86.67% and 89.12%) and splenic (95.45% and 95.84%) parasite burden with decrease in spleen weight was observed. AAL and AAS treated mice induced the strongest DTH response, as well as three-fold decrease in IgG1 and two-fold increase in IgG2a levels, as compared to infected controls. Cytometric bead array further affirmed the elicitation of Th1 immune response as indicated by increased levels of IFN-γ, and low levels of Th2 cytokines (IL-4 and IL-10) in serum as well as in culture supernatant of lymphocytes from treated mice. Lymphoproliferative response, IFN-γ producing CD4+ and CD8+ T lymphocytes and nitrite levels were significantly enhanced upon antigen recall in vitro. The co-expression of CD80 and CD86 on macrophages was significantly augmented. CD8+ T cells exhibited CD62Llow and CD44hi phenotype, signifying induction of immunological memory in AAL and AAS treated groups. Serum enzyme markers were in the normal range indicating inertness against nephro- and hepato-toxicity. CONCLUSIONS/SIGNIFICANCE:Our results establish the two-prong antileishmanial efficacy of AAL and AAS for cure against L. donovani that is dependent on both the direct leishmanicidal action as well as switching-on of Th1-biased protective cell-mediated immunity with generation of memory. AAL and AAS could represent adjunct therapies for the treatment of leishmaniasis, either alone or in combination with other antileishmanial agents.